Adherence to diabetic self-care management and associated factors among type 2 diabetic patients in North Shewa Zone public hospitals in Amhara Region, Ethiopia - Endale, Agizew; Hundessa, Fitsum; Tamru, Eyasu; Nigussie, Fetene; Hailu, Minyahl (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionAdherence to diabetes self-care management is a lifestyle modification for people with diabetes.ObjectiveTo assess adherence to diabetic self-care management and associated factors among type 2 diabetic patients in North Shewa Zone public hospitals, Ethiopia, 2023.MethodsThe study employed a concurrent mixed-methods approach among 600 type 2 diabetic patients in North Shewa Zone public hospitals in Amhara, Ethiopia. The study was conducted from May 5 to May 20, 2023. The quantitative data were collected by using a semi-structured interview-administered questionnaire and chart review. Logistic regression was employed, and a p-value < 0.05 was considered statistically significant. Qualitative data were collected by in-depth interviews, and audio recordings were first transcribed verbatim and then translated to the English language by the first author and analyzed manually using a thematic approach.ResultOut of the total 600 type 2 diabetic patients, 262 (43.7%) with 95% CI: 40–47.8% of the study participants had good adherence to diabetes self-care practices. The multivariable analysis indicated that type 2 diabetic patients who lived in urban areas [AOR: 5.4, 95% CI: (1.05-8.7)] were 5.4 times more likely to have good diabetic self-care practice than those rural residents. Those who had a high school level of education [AOR: 2.9, 95% CI: (1.3-6.6)] were 2.9 times more likely to have good self-care practice, and those with college and above [AOR: 5, 95% CI (2–12):] were five times more likely to have good self-care practice. Regarding occupation, unemployed people were 66% less likely to have good self-care practices than employed people. Those who had no availability of healthcare services [AOR: 0.19, 95% CI: (0.09-0.37)] were less likely by 81% to have good self-care practice than those who had availability of healthcare services. These are significantly associated with diabetic self-care practice. The qualitative component clarified six themes: lack of education and awareness, financial affordability, accessibility, lack of family support, and having diabetic-related complications were identified as barriers.ConclusionThis study indicated that adherence of patients with type 2 diabetes to the recommended self-care practices was considerably poor. Different factors included the respondents who had a high school level or higher level of education and those who lived in urban areas. This was supported by the results from the qualitative part and thus the endorsement to strengthen diabetes health education to patients and their families. So, diabetic patients require an integrated approach through treatment as well as health education, which will increase the health and well-being of the patient.